Experimental study on the energy flow of a commercial heavy-duty vehicle under the C-WTVC of cold and warm start. (15th November 2022) - Ma, Qixin; Zhang, Quanchang; Liang, Jichao; Chen, Zheng
Highlights: Continuous acceleration and deceleration lead to more unnecessary coolant energy loss because of increases the coolant temperature variation range. Compared the sensitivity of coolant flow with the change of vehicle speed under the warm start, the coolant flow has a great lag under cold start. The torque is mainly distributed in the medium region, while speed range is from 1100 to 1400 rpm under C-WTVC. Keeping the vehicle in a stable running condition is beneficial to improve the effective thermal efficiency. Abstract: In order to improve the actual performance of China-VI heavy-duty vehicle (HDV), the energy flow test on a HDV was conducted under the C-WTVC (Chinese-World Transient Vehicle Cycle). Then, the transient energy distribution of heavy-duty diesel engine was compared with different start condition. Results show that, the energy flow is greatly affected by the variation of actual vehicle conditions. The percentage of coolant energy fluctuates between 6% and 76%. In the urban cycle, the exhaust energy is slightly higher under cold start condition due to the high engine speed at the beginning of this condition. In the expressway cycle, the coolant loss ratio fluctuates slightly and stabilizes around 20% and the percentage of exhaust energy is around 32% in the later constant speed stage. What's more, idle and variable working conditions can cause a large energy loss, such as the acceleration and deceleration of C-WTVC. All those provide guidance for improving the actual energy efficiency of HDVs.